The Sodium Sialic Acid Symporter From Staphylococcus aureus Has Altered Substrate Specificity - North, Rachel A.; Wahlgren, Weixiao Y.; Remus, Daniela M.; Scalise, Mariafrancesca; Kessans, Sarah A.; Dunevall, Elin; Claesson, Elin; Soares da Costa, Tatiana P.; Perugini, Matthew A.; Ramaswamy, S.; Allison, Jane R.; Indiveri, Cesare; et al. (Frontiers in Chemistry, 2018)
Mammalian cell surfaces are decorated with complex glycoconjugates that terminate with negatively charged sialic acids. Commensal and pathogenic bacteria can use host-derived sialic acids for a competitive advantage, but require a functional sialic acid transporter to import the sugar into the cell. This work investigates the sodium sialic acid symporter (SiaT) from Staphylococcus aureus (SaSiaT). We demonstrate that SaSiaT rescues an Escherichia coli strain lacking its endogenous sialic acid transporter when grown on the sialic acids N-acetylneuraminic acid (Neu5Ac) or N-glycolylneuraminic acid (Neu5Gc). We then develop an expression, purification and detergent solubilization system for SaSiaT and demonstrate that the protein is largely monodisperse in solution with a stable monomeric oligomeric state. Binding studies reveal that SaSiaT has a higher affinity for Neu5Gc over Neu5Ac, which was unexpected and is not seen in other SiaT homologues. We develop a homology model and use comparative sequence analyses to identify substitutions in the substrate-binding site of SaSiaT that may explain the altered specificity. SaSiaT is shown to be electrogenic, and transport is dependent upon more than one Na+ ion for every sialic acid molecule. A functional sialic acid transporter is essential for the uptake and utilization of sialic acid in a range of pathogenic bacteria, and developing new inhibitors that target these transporters is a valid mechanism for inhibiting bacterial growth. By demonstrating a route to functional recombinant SaSiaT, and developing the in vivo and in vitro assay systems, our work underpins the design of inhibitors to this transporter.